Monitoring of Anxiety-Like Behaviors on Rats with Video Tracking Technology - Ayşen ÇETIN KARDEŞLER; Meriç ÇETIN; Selami BEYHAN (International Journal of Applied Methods in Electronics and Computers, 2016)
Artificial sweeteners like MSG (Mono Sodium Glutamate) model has been used anxiety-like behaviors on rats. The tracking of rat’s movements has broad applicability to questions in anxiety-like behaviors with different doses MSG injections (50 mg/kg/day, 100 mg/kg/day and 200 mg/kg/day) to rats. In this paper, in order to measure three types locomotor activity (line crossing, rearing, grooming), a video tracking software is used. The advantage of this type of tracking software is that it provides to give locomotor activity of rats in real-time. The experimental results obtained in this study have shown that learning and memorial functions negatively affected in the brains of the rats an anxiety-like model. In addition, the visual tracking results demonstrate that video tracking system provides an accurate monitoring of rat’s behavior.